2018
DOI: 10.1515/med-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for physician burnout: A systematic review

Abstract: AbstractBurnout is an important problem for physicians, with a strong impact on their quality of life and a corresponding decrease in the quality of care with an evident economical burden for the healthcare system. However, the range of interventions used to decrease this problem could be very fragmented and with the aim to shed some light on this issue, this study reviews and summarizes the currently available studies. We conducted a systematic review using the Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 70 publications
3
153
0
7
Order By: Relevance
“…It was observed that the frenetic was an engaged profile, and thus, it was opposed to both the under-challenged and worn-out, which shared a certain lack of engagement. This suggests the frenetic could be a prodrome that may end up being worn-out [95] while the under-challenged might follow a different-but not less relevant-way in the burnout development process. Finally, we have found the burnout subtypes were differentially related to sociodemographic and occupational variables (hypothesis 5).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the frenetic was an engaged profile, and thus, it was opposed to both the under-challenged and worn-out, which shared a certain lack of engagement. This suggests the frenetic could be a prodrome that may end up being worn-out [95] while the under-challenged might follow a different-but not less relevant-way in the burnout development process. Finally, we have found the burnout subtypes were differentially related to sociodemographic and occupational variables (hypothesis 5).…”
Section: Discussionmentioning
confidence: 99%
“…Physician burnout is a public health crisis and the problem is growing. [55][56][57][58][59] ''Not only does the individual suffer decreased self-esteem and a sense of failure, but his or her ability to provide care can be diminished, as can the ability to work with staff and colleagues. Absenteeism, lower productivity, and higher turnover, with subsequent disruptions in patient care continuity and patient disenrollment, can occur.''…”
Section: Physicians From Underrepresented Groups and Risk For Leavingmentioning
confidence: 99%
“…These differences in satisfaction may help to explain why PGY1 residents in the additional PGT group sought out additional training; overall, they were experiencing greater satisfaction at the midpoint of their PGY1 experience. While residents in the additional PGT group may be more commonly classified as feeling overextended, it is likely that the tiredness and stress found in those with high exhaustion were better managed because those residents remained proud of their accomplishments and were not detached from those they were interacting with during their training . This may help to validate the presence of the often‐seen trope: the busy and tired trainee continues to forge ahead toward additional training as long as their attitude and relationships remain adequate .…”
Section: Discussionmentioning
confidence: 99%
“…While residents in the additional PGT group may be more commonly classified as feeling overextended, it is likely that the tiredness and stress found in those with high exhaustion were better managed because those residents remained proud of their accomplishments and were not detached from those they were interacting with during their training . This may help to validate the presence of the often‐seen trope: the busy and tired trainee continues to forge ahead toward additional training as long as their attitude and relationships remain adequate . However, residency preceptors and program directors should be cognizant of shifts in these overextended residents' attitudes as they could move into becoming burned out without proper support.…”
Section: Discussionmentioning
confidence: 99%